Reconstruction of Large Full-Thickness Abdominal Wall Defects Using a Free Functional Latissimus Dorsi Muscle - Ninkovic, Marijana; Ninkovic, Marina; Öfner, Dietmar; Ninkovic, Milomir (Frontiers in Surgery, 2022)
Introduction: The large full-thickness abdominal wall defect has to be treated by considering anatomical and functional requirements. The abdominal wall must regain total physiological function, which means that the full thickness abdominal wall defect must be reconstructed anatomically, not only according to the anatomical requirements but keeping functional dynamic voluntary movement. Defects in the abdominal wall alter respiratory mechanics and can impair diaphragm function. Additionally, muscles of the anterolateral abdominal wall increase the stability of the lumbar region of the vertebral column by tensing the thoracolumbar fascia and by increasing intra-abdominal pressure. Materials and Methods: The timing, and method of reconstruction must be chosen depending upon the etiology of the defect. Severe traumatic injuries, abdominal wall infections, necrotizing soft tissue loss or sepsis needs to undergo staged reconstruction following adequate debridement to control the infectious process, establish the zone of injury and proper treatment of intraabdominal pathology, achieving temporary primary closure using split-thickness skin grafting to the viscera. At the time of definitive reconstruction deep skin graft dermabrasion, give us a facial like layer, with adequate strength to stabilize statically abdominal wall. This dermal layer is supported by free functional (innervated) latissimus dorsi muscle (fLDM) giving full anatomical coverage and functional stability. After oncologic resections full-thickness abdominal wall reconstruction was performed immediately with a combination of fLDM flaps and meshes. Results: 14 Patients underwent abdominal wall reconstruction using fLDM flap. Staged reconstruction was applied in 8 cases. In the additional six cases, two had no mesh support, three had synthetic mesh, and one had a fascial graft, which were covered with fLDM flap. There were no free flaps failure. One flap revision due to venous anastomosis thrombosis was performed. Donor site seromas occurred in 5 cases and were treated with punction and direct Doxycycline injection. Electromyographic testing postoperatively confirmed reinnervation of transplanted LDM. Conclusion: Using fLDM as a definitive solution, we are not only able to repair soft tissue defect, but also to reconstruct voluntary contractility and dynamic natural functional abdominal wall. Transplanted LDM offers enough contractile capacity and strength to replace the function of the missing abdominal wall muscles.